The identity of Kelantan peranakan Chinese through clothing: An aesthetic morphology approach - Hanisa Hassan; Nasirin Abdillah; Mohd Zaimmudin Mohd Zain; Siti Nur Anis Apandi; Nik Maheran Nik Muhammad (AIP Publishing, 2021)
The term, ‘peranakan’ refers to a community that traces its lineage to the first waves of Hoklo (Han Chinese) settlers who interacted, especially through marriage, with the local people of the Malay Peninsula and Indonesian Archipelago. There are various types of the Peranakans in Malaysia such as the Baba-Nyonya, Chitty, Kristang (mostly in Melaka) and other Peranakan Muslims of Indian, Malay and Arab descent known as Jawi Peranakan. The Kelantan Peranakan Chinese (also known as Cina Peranakan Kelantan in Malay) is another unique ethnic group of Peranakans characterised by its mixture of three cultures: the local Malay of Kelantan, Chinese and Thai. However, this acculturated ethnicity seems to be less appreciated by the younger generation of the Kelantan Peranakan Chinese. One of the reasons is perhaps due to a general perception of the Kelantanese people that label them as cina kampung or cina bukit. To the older generation of the Kelantan Peranakan Chinese, they are proud to be called cina kampung whereas the younger generation may view this term as derogatory, implying that they are not advanced or modern people. The dwindling sense of pride among the younger generation may have resulted in the dying culture of the Kelantan Peranakan Chinese. A diluting image in their cultural artefacts is a case in point. Clothing, which is one of the important cultural artefacts, is gradually forgotten by the younger generation. Modern clothing is more appealing to them compared to the simplicity of clothing worn by their elder folks in the kampung (village). This study is aimed at examining the clothing of the Kelantan Peranakan Chinese, particularly, by studying its components of design elements using the aesthetic morphology approach. The formalistic aspect of the clothing, for instance, the ubiquitous paired blouse and sarong are a reflection of three cultural amalgamation of Malay, Chinese and Thai. The aesthetic aspect is also shown through their humble way of clothing hence symbolising a simple way of life of the community of Kelantan Peranakan Chinese. The finding thus concludes that the form and style of clothing worn by the Kelantan Peranakan Chinese is distinctive from other Peranakans in different states of Malaysia. REFERENCES